Patient‐reported outcomes for congenital diaphragmatic hernia: A qualitative study. (21st January 2023) - Taillieu, Aymara; Deprest, Jan; Vergote, Simen; Debeer, Anne; Russo, Francesca Maria; Power, Beverley; Meijer, Frank; Crombag, Neeltje
Abstract: Objective: To identify Patient‐reported outcomes (PROs) for parents with a lived experience of a prenatal diagnosis of isolated congenital diaphragmatic hernia (CDH). Method: Thematic analysis of in‐depth interview transcripts. Results: Interviews ( n  = 26) identified 11 PROs for given time points throughout the CDH trajectory. At the time of diagnosis, acceptable quality of life was selected as relevant PRO to decide whether to continue or terminate the pregnancy. During pregnancy, ( neonatal ) survival chances and the eligibility for foetal therapy were prominent outcomes with foetal and maternal complications adding distress. After birth, postnatal management options became the next milestone. When survival was deemed likely, post‐hospital discharge complications and future care for infant and child became important. In retrospect, impact on family, bonding, parental mental health, and parental satisfaction with care were reported as relevant outcomes. Conclusion: PROs are relevant in addition to hard medical outcomes, as they help parents to make decisions suiting their unique needs and personal situation. Given the knowledge inherently related to the parent's perspective, our findings provide relevant directions for clinicians to support parents and their family in facing challenging decisions in healthcare. The outcomes impacting parents are essential to prepare parents for the steep journey ahead. Key points: What's already known about this topic? Following a prenatal diagnosis of congenital diaphragmatic hernia (CDH), parents are faced with many uncertainties regarding the eventual outcomes of their future child and therefore need continuous multidisciplinary care (from diagnosis to at least post‐discharge), involving support in making informed decisions; Patient‐reported outcomes (PROs) have been identified in other settings to provide and enhance patient‐centred care. What does this study add? This study identified PROs of parents with a lived experience of a having a baby with CDH for different time points during pregnancy and the neonatal period; The PROs indicate additional information relevant to parents, such as the child's quality of life (QoL), the impact on the family, bonding, parental mental health, and parental satisfaction with care; These PROs are an addition to hard medical outcomes and can help parents in making informed decisions suiting their unique needs and personal situation.